2017
DOI: 10.12739/nwsa.2017.12.2.5a0084
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF ANTIBACTERIAL ACTIVITY OF MACERATED OIL FROM Lemon Balm, Thyme (Thymus vulgaris L, Lamiaceae), Mint (Mentha longifolia L, Lamiaceae) and Marigold WITH MODIFIED TUBE AGAR DILUTION METHOD AGAINST YERSINIA RUCKERI

Abstract: Aromatic and medicinal plants (AMPs) have been most popular for human and animal in phytotherapy, phytochemistry and pharmacology recently owing to their anti-bacterial, anti-viral, and antiseptic characteristics. Therefore, experiments were designed for determination the antibacterial effects of macerated and distilled oils of lemon balm (Melissa officinalis), thyme (Thymus vulgaris), mint (Mentha longifolia) and marigold (Calendula officinalis) against Yersinia ruckeri with modified tube agar dilution method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Plant extracts can be utilized alone or in combination with other extracts, requiring minimal processing, to achieve synergistic effects in meat and meat products. Recent studies have demonstrated that clove and cinnamon oils ( Adhikari et al, 2021 ; Feng et al, 2022 ), thyme and balsam oils ( Fratianni et al, 2010 ; Altınterim and Kocabaş, 2017 ), as well as hops extracts ( Kramer et al, 2015 ; Arruda et al, 2021 ) exhibit excellent inhibitory effects against meat spoilage bacteria. Plant extracts are generally recognized as safe ( GRAS ) and are preferred by most consumers over synthetic preservatives.…”
Section: Development Of Functional Fermented Poultry Meat Productsmentioning
confidence: 99%
“…Plant extracts can be utilized alone or in combination with other extracts, requiring minimal processing, to achieve synergistic effects in meat and meat products. Recent studies have demonstrated that clove and cinnamon oils ( Adhikari et al, 2021 ; Feng et al, 2022 ), thyme and balsam oils ( Fratianni et al, 2010 ; Altınterim and Kocabaş, 2017 ), as well as hops extracts ( Kramer et al, 2015 ; Arruda et al, 2021 ) exhibit excellent inhibitory effects against meat spoilage bacteria. Plant extracts are generally recognized as safe ( GRAS ) and are preferred by most consumers over synthetic preservatives.…”
Section: Development Of Functional Fermented Poultry Meat Productsmentioning
confidence: 99%